ACTIVITY OF DAILY LIVING: LONG-STAY INSTITUTION FOR THE ELDERLY (Fiep Bulletin - online, 2024)
AbstractThe elderly need social assistance and medical priority. It is important to monitor the independence of the elderly in their daily lives and to respect them as human beings. The aim of this study was to analyze the level of independence in activities of daily living (ADLs) of a group of elderly people living in LSIEs (Long Stay Institutions for the Elderly). Eleven elderly people aged 60 or over took part in this study. This is a descriptive quantitative study that establishes associations between variables such as gender, age, recreational and leisure activities, health problems and self-perception. Data obtained from the questionnaire and descriptive statistics were used for the calculations. We found that the condition of independence of the elderly in leisure activities does not affect their ability to stabilize or reverse the age-related decline in physical activity. We know that health problems can influence poor performance in ADLs. However, elderly people with pathologies have the autonomy to perform some of the ADLs independently, but older men have greater independence compared to women, and those aged between 80 and 89 are more independent than those aged between 70 and 79. Elderly people of both sexes have a perception of their independence and reduced motor skills in performing certain ADLs, especially among those aged between 80 and 89.
Keywords: Elderly; ADLs; LSIEs